DILEMA PENGGUNAAN SYI'IR JAHILIYYAH DALAM TAFSIR "Kajian Atas Pemikiran Thaha Husein" - Mohammad Azza Nasrul Khobir (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
This article exposes on Thaha Husain’s thoughts on the authenticity of the pre-Islamic poetry descriptively by investigating his arguments in his famous book Fi al-Syi’ri al-Jahili (On Pre-Islamic Poetry) which was then changed into Fi al-Adab al-Jahili (On Pre-Islamic Literature) with some revisions. This study mainly discusses the authenticity of the pre-Islamic poetry, its urgency in interpreting the Qur’an, and how the Qur’an views pre-Islam Arab society. It is revealed in the article that a lot of pre-Islamic poetry was not composed in the era of ignorance (Jahiliyah) by pre-Islamic Arab poet but by plagiarists in the era of Abbasiyah Empire for some purposes: political, religion, Qishshah and Hadith narrators. According to Thaha Husain, that a lot of the pre-Islamic poetry neither fit in with pre-Islam Arab nor describe objectively pre-Islam Arab society. It is sufficient to refer to the Qur’an, which certainly valid, to obtain objective descriptions of the pre-Islamic Arab society.